Real and Imagined Grasping Movements Differently Activate the Human Dorsomedial Parietal Cortex. (10th May 2020) - Sulpizio, Valentina; Neri, Anna; Fattori, Patrizia; Galletti, Claudio; Pitzalis, Sabrina; Galati, Gaspare
Highlights: The human dorsomedial parietal cortex responds to pantomimed grasping movements. Areas hV6A and hPEc are differently activated by real and imagined grasping movements. Areas hV6Ad and hPEc are respectively involved in cognitive and pragmatic aspects of the control of grasping. Abstract: Object prehension typically includes a transport phase (reaching) and a grip phase (grasping). Within the posterior parietal cortex (PPC), grasping movements have been traditionally associated to a lateral activation, although recent monkey evidence suggests also a medial involvement. Here, we wanted to determine whether grasping-related activities are present in the human dorsomedial parietal cortex, by focusing on two cortical regions specialized in the monkey in controlling limb movements, i.e., V6A (composed by its ventral and dorsal sectors, V6Av and V6Ad, respectively) and PEc, both recently defined also in humans. We acquired functional magnetic resonance images while participants performed both real (pantomimed) and imagined grasping of visually-presented objects. We found that the human areas V6Ad (hV6Ad) and PEc (hPEc) were both activated by real grasping, whereas hV6Ad only was activated by the imagery of grasping movements. hV6Av was not involved in either types of grasping. These results speak against the traditional notion of a medial-to-lateral segregation of reaching versus grasping information within the PPC and strengthen the idea that the human dorsomedial parietal cortex implements the whole complex pattern of visuomotor transformations required for object-oriented actions. Our findings suggest that hV6Ad is particularly involved in implementing all the visuomotor transformations needed to create an abstract representation of the object-directed action, while hPEc is involved in implementing the sensorimotor transformations needed to actually perform that action.